Developing a model for ecclesiastical discipline in the Church of Pentecost-Ghana - Mzondi, Modisa; Kumi-Woode, Benjamin (Stellenbosch Theological Journal, 2024)
This article presents some of the findings of doctoral empirical study on ecclesiastical discipline in the Church of Pentecost-Ghana, over the past thirty years, with a view to developing a model of ecclesiastical discipline for the church. Osmer’s (2008) approach is applied to assist developing the envisaged model. Thus, the article asks: What model of ecclesiastical discipline can be established for the Church of Pentecost–Ghana? Thirty participants, including ministers, elders, and members of the Ghana Conference of the Parties in Accra, were interviewed. The participants viewed ecclesiastical discipline as relevant to the Church of Pentecost-Ghana to show the church, Christ’s bride, as holy and to protect the church’s reputation and aid it in fulfilling its divine mandate of preparing Christ’s return. They raised concerns regarding the application of ecclesiastical discipline in the Church of Pentecost–Ghana, as well as suggested some suitable approaches in ecclesiastical discipline in the church. The researcher then developed a model based on the concerns and suggestions of the participants.